1996
DOI: 10.1149/1.1837188
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Thin‐Film Rechargeable Lithium Batteries with Lithium Cobalt Oxide Cathodes

Abstract: Thin-film rechargeable lithium batteries with amorphous and crystafline LiCoO2 cathodes were investigated, The lithium cobalt oxide films were deposited by radio-frequency (RF) magnetron sputtering of an LiCoO2 target in a 3:1 Ar/02 mixture gas. From proton-induced -y-ray emission analysis (PIGE) and Rutherford backscatterung spectrometry (RBS), the average composition of these films was determined to be Li115CoO216 or, within experimental uncertainty, LiCoO2 + 0.08 Li20. The x-ray powder diffraction patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
241
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(251 citation statements)
references
References 6 publications
9
241
1
Order By: Relevance
“…The voltage profiles show that the discharge capacity was improved from 79.8 mA·h·g −1 in the sample calcined at 400 • C to 131 mA·h·g −1 in the one at 900 • C with increasing calcination temperature. This result is in good agreement with our XRD results, indicating that high temperature calcination induces a high degree of cation ordering [31,36]. It has been reported that the Li ion inserts more efficiently for a sample with a lower degree of cation ordering in a textured electrode structure thanks to a greater number of electrochemical active sites and a shorter diffusion length than a sample with a higher degree of cation ordering [30,35,37].…”
Section: Electrochemical Characterizationsupporting
confidence: 92%
“…The voltage profiles show that the discharge capacity was improved from 79.8 mA·h·g −1 in the sample calcined at 400 • C to 131 mA·h·g −1 in the one at 900 • C with increasing calcination temperature. This result is in good agreement with our XRD results, indicating that high temperature calcination induces a high degree of cation ordering [31,36]. It has been reported that the Li ion inserts more efficiently for a sample with a lower degree of cation ordering in a textured electrode structure thanks to a greater number of electrochemical active sites and a shorter diffusion length than a sample with a higher degree of cation ordering [30,35,37].…”
Section: Electrochemical Characterizationsupporting
confidence: 92%
“…Another useful method is an electrochemical measurement with a thin film of active material. 11,12 However, some active materials cannot be prepared in a thin film form due to chemical characteristics of materials. In addition, the thin films of active materials are not exactly same with the particles of active materials used in practical batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The successive reduction of both S 2− and Fe 2+ species led to an impressive volumetric discharge capacity, five times higher than the one for LiCoO 2 . Excellent reversibility and capacity retention were obtained during the first and the subsequent 800 charge-discharge cycles.…”
Section: Introductionmentioning
confidence: 85%